THE MEANING OF KUMAWUS CULTURE IN THE TRADITIONS OF THE MINAHASA COMMUNITY: Makna Budaya Kumawus dalam Tradisi Masyarakat Minahasa - Tatiana Bolang; Ilke J. Moniung; Dina Ch. M. Rottie (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The Kumawus tradition is one of the traditions in the Minahasa region created by the ancestors of the Minahasa tribe. This study aims to explore in-depth knowledge of family activities in the implementation of Kumawus and to explain the symbolic meaning contained in this tradition. The method used is descriptive with primary and secondary data sources, this study uses survey techniques, direct observation with interview instruments. The research location is in the Minahasa Regency of North Sulawesi. Data analysis was carried out through qualitative data analysis. This study produces a form of positive cultural meaning, through the tradition in the Kumawus activity which is one form of community efforts to maintain regional culture, amidst the rapid flow of modern socio-cultural changes. In the Kumawus activity, the community is involved, especially the younger generation, to explore the symbolic meaning in socio-cultural and religious culture that is interpreted personally, family and in the community environment as local wisdom in the Minahasa region.